Association between FOXP3 polymorphisms and susceptibility to autoimmune diseases: A meta-analysis. (3rd October 2015) - Lee, Min-Gu; Bae, Sang-Cheol; Lee, Young Ho
Abstract: Objective : The aim of this study was to explore whether the FOXP3 −3279 A/C polymorphism and (GT) n microsatellite polymorphisms are associated with susceptibility to autoimmune diseases. Methods : A meta-analysis was conducted on the associations between the FOXP3 −3279 A/C polymorphism and (GT)15 and (GT)16 polymorphisms and autoimmune diseases. Results : Twenty-two comparative studies with a total of 7962 patients and 7453 controls were included in the meta-analysis. Meta-analysis revealed an association between autoimmune disease and the FOXP3 −3279 AA + AC genotype (OR = 1.480, 95% CI = 1.263–1.614, p < 1.0 × 10 −9 ), and stratification by ethnicity indicated a significant association between the FOXP3 −3279 AA + AC genotype and autoimmune diseases in Asians (OR = 1.416, 95% CI = 1.225–1.637, p = 2.5 × 10 −7 ) and non-Caucasians (OR = 1.432, 95% CI = 1.245–1.647, p = 7.5 × 10 −8 ). In addition, corrected p values for multiple testing remained significant. Meta-analysis revealed no association between autoimmune disease and the FOXP3 (GT)15 allele (OR = 1.051, 95% CI = 0.933–1.183, p = 0.413). Similarly, the FOXP3 (GT)16 allele showed no associations with autoimmune disease. Conclusions : This meta-analysis indicates that the FOXP3 −3279 A/C polymorphism is associated with susceptibility to autoimmune disease in Asians and non-Caucasians.